The Influence of Managerial Competence and Supervisory Competence on the Performance Management Ability of Elementary School - Nurmayanti Nurmayanti; Syahrul Syahrul; Baso Intang Sappaile (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study aims to analyze the influence of managerial competence and supervisory competence on the performance management ability of elementary school principals in Bontomanai District, Selayar Islands Regency. This study uses a quantitative approach with a correlational design. The research population consists of all elementary school principals in the area, with the sampling technique using total sampling. Data were collected thru structured questionnaires and analyzed using descriptive statistics and multiple regression analysis. The research results show that managerial competence has a positive and significant effect on the performance management ability of school principals. Supervisory competence also has a positive and significant effect on performance management ability. Simultaneously, both competencies significantly contribute to enhancing the effectiveness of school principals in managing school performance. These findings underscore the importance of strengthening managerial and supervisory competencies to enhance the quality of leadership and overall school performance. Therefore, it is recommended that the relevant parties provide continuous professional development programs focused on enhancing managerial and supervisory competencies for school principals.